Linking microbial heterotrophic activity and sediment lithology in oxic, oligotrophic subseafloor sediments of the North Atlantic Ocean - Picard, Aude; Ferdelman, Timothy G. (Frontiers in Microbiology, 2011)
Microbial heterotrophic activity was investigated in oxic subseafloor sediments at North Pond, a sediment pond situated at 23°N on the western flank of the Mid-Atlantic Ridge. The North Pond sediments underlie the oligotrophic North Atlantic Gyre at 4580 m water depth and cover a 7-8 million year-old basaltic crust aquifer through which seawater flows. Discrete samples for experimentation were obtained from up to 9 m-long gravity cores taken at 14 stations in the North Pond area. Potential respiration rates were determined in sediment slurries incubated under aerobic conditions with 14C-acetate. Microbial heterotrophic activity, as defined by oxidation of acetate to CO2 (with O2 as electron acceptor), was detected in all 14 stations and all depths sampled. Potential respiration rates were generally low (< 0.2 nmol of respired acetate cm-3 d-1) in the sediment, but indicate that microbial heterotrophic activity occurs in deep-sea, oxic, sub-seafloor sediments. Furthermore, discernable differences in activity existed between sites and within given depth profiles. At 7 stations, activity was increased by several orders of magnitude at depth (up to 12 nmol of acetate respired cm-3 d-1). We attempted to correlate the measures of activity with high resolution color and element stratigraphy. Increased activities at certain depths may be correlated to variations in the sediment geology, i.e. to the presence of dark clay-rich layers, of sandy layers, or within clay-rich horizons presumably overlying basalts. This would suggest that the distribution of microbial heterotrophic activity in deeply buried sediments may be linked to specific lithologies. Nevertheless, high resolution microbial examination at the level currently enjoyed by sedimentologists will be required to fully explore this link.